ANALYSIS OF FACTORS AFFECTING THE LEVEL OF SHARES IN OFFER UNDERPRICING PRIME STOCK EXCHANGE IN JAKARTA - Martanto, Heru; Nursasmita, Ak., Drs. H. Irfan (Accounting, 2009)
This study tested the hypothesis that was developed in the context of asymmetric information among market players in the Indonesian capital market. The hypothesis proposed in this research is the influence of market conditions, the reputation of underwriters, auditor reputation, and influence of these three variables simultaneously on the level of underpriced. Dat collection methods using secondary data, and is used as a sample of 36 companies from 2002 to 2004. Sources of data obtained from the Indonesian Capital Market Directory, the JSX Statistics, and FE UGM PPA database. Data analysis techniques used are simple regression analysis of single and double. In processing the data using SPSS. The results showed that the market conditions and reputation of the auditor does not affect negatively. While the underwriter reputation and the use of these three variables (market conditions, underwriter reputation, and reputation of the auditor) is jointly negative effect, this means that if something else fixed, the higher reputation underwriter will cause a decrease in initial returns. Keywords: Indonesia´s capital market, capital market participants.